2019
DOI: 10.2807/1560-7917.es.2019.24.10.1800407
|View full text |Cite
|
Sign up to set email alerts
|

HEVnet: a One Health, collaborative, interdisciplinary network and sequence data repository for enhanced hepatitis E virus molecular typing, characterisation and epidemiological investigations

Abstract: Hepatitis E virus (HEV) is a common cause of acute hepatitis worldwide. In Europe, HEV is a zoonosis transmitted via contaminated pork meat or other pork food products. Genotype 3 is the most prevalent HEV type in the animal reservoir, as well as in humans. Despite an increased incidence of hepatitis E across Europe, much remains unknown about its spread, sources and transmission routes. A One Health approach is crucial to better understand the (molecular) epidemiology of HEV. HEVnet was established in April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 17 publications
0
46
0
Order By: Relevance
“…An accessible and standard methodology for subtype allocation is important so that researchers can assign strains to particular subtypes. Online tools that have recently become available for the genotyping and subtyping of HEV sequences include HEV-GLUE (http://hev.glue.cvr.ac.uk) [26] and HEVnet (https://www.rivm.nl/mpf/typingtool/hev/) [27]. These tools can be used to make subtype assignments based on the analysis of HEV subgenomic sequences.…”
Section: Discussionmentioning
confidence: 99%
“…An accessible and standard methodology for subtype allocation is important so that researchers can assign strains to particular subtypes. Online tools that have recently become available for the genotyping and subtyping of HEV sequences include HEV-GLUE (http://hev.glue.cvr.ac.uk) [26] and HEVnet (https://www.rivm.nl/mpf/typingtool/hev/) [27]. These tools can be used to make subtype assignments based on the analysis of HEV subgenomic sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus sequence was obtained using Seqman Software SeqMan NGen® Version 12.0 (DNASTAR). Subtype assignment and phylogenetic analyses were performed using the HEVnet genotyping tool (https://www.rivm.nl/mpf/typingtool/hev/) (Mulder et al, ) and confirmed by BLAST. Sequence alignments were generated by the MAFFT online service: multiple sequence alignment, interactive sequence choice and visualization.…”
Section: Methodsmentioning
confidence: 99%
“…Reference HEV-3 sequences of established and recently proposed subtypes (n = 15) (Smith et al, 2016;Miura et al, 2017;De Sabato et al, 2018) were included in the tree for the HEV-3 assignment. Those sequences not belonging to any subtypes defined so far were aligned with sequences of the HEVnet dataset (Mulder et al, 2019) using the public HEVnet typing tool 3 .…”
Section: Phylogenetic Analysismentioning
confidence: 99%